STRATEGI REVITALISASI BUMDES DI DESA KALIKAJAR KECAMATAN KALIGONDANG KABUPATEN PURBALINGGA - Chamid Sutikno; Ikmas Ma’mur Alfani (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2022)
Villages have an important role in national development, therefore villages are a serious concern for the development of a country. Village independence can grow productive community groups, along with decentralization and regional autonomy which will support community development and empowerment through the local economy, one of which is through BUMDES. This study took the title BUMDES Revitalization Strategy in Kalikajar Village, Kalikabong District, Purbalingga Regency using qualitative descriptive research methods. Sources of data in this study are secondary data and primary data. The purpose of this study is to find out about the strategies and factors driving the revitalization of BUMDES Kalikajar, Kaligondang District, Purbalingga Regency. Keywords; SWOT Analysis, BUMDes Revitalization, Institutional Strategy